A DESCRIPTIVE STUDY TO DEVELOP A TOOL FOR THE ASSESSMENT OF SATVA SAARA - Aswathy V.; Abhilash M.; Nikhil M Kumar (International Journal of Applied Ayurved Research, 2018)
Present study titled ‘Descriptive study to develop a tool for the assessment of Satvasaara’is a methodological psychometric research work. The objective of the study was to develop a valid and reliable tool for the assessment of Satvasara. Satvasaara gives a measure of excellence in function of mind, which is important in diagnostic and treatment aspects. The tool development was carried out satisfying all necessary steps in a systematic way from conceptualization for identification of variables, operationalisation, item generation, item reduction, item wording and sequencing, translation and back translation, pretest, pilot study, item reduction to final administration of the tool. Content validity and face validity was obtained by expert valuation. In order to obtain concurrent validity, tool was compared with Emotional Intelligence Inventory, a validated tool to measure emotional intelligence. To ensure construct validity, factor analysis was done. The statistical method of fixation of base line for dividing groups into Pravara Madhayama and Avara saara was also detailed and the final tool is attached to the end of article.